Retinopathy of prematurity as a major cause of severe visual impairment and blindness in children in schools for the blind in Guadalajara city, Mexico. Issue 11 (7th June 2011) - Zepeda-Romero, L C; Barrera-de-Leon, J C; Camacho-Choza, C; Gonzalez Bernal, C; Camarena-Garcia, E; Diaz-Alatorre, C; Gutierrez-Padilla, J A; Gilbert, C
Abstract : Aim: To determine the causes of blindness in students attending schools for the blind in Guadalajara city, Mexico and to assess the availability of screening for retinopathy of prematurity (ROP) in local neonatal intensive care units. Methods: Information on causes of blindness was obtained by interview with parents and teachers, review of records and examination. Causes of visual loss in children with a distance visual acuity of <6/60 (ie, severely visually impaired or blind) were determined and classified according to the WHO's classification system for children. Results: Of 153 children in the two participating schools, 144 were severely visual impaired or blind. Their ages ranged from 4 months to 15 years and 58% were female. ROP was the most common cause of visual loss (34.7%), followed by optic nerve lesions (17.4%) and glaucoma (14.6%). 25/59 (42.3%) children aged 0–4 years were blind from ROP compared with 6/32 (18.8%) children aged 10–15 years. 78% of children blind from ROP had psychomotor delay and less than half (46%) had not received treatment for ROP. All five privately funded neonatal intensive care units in the city regularly screen for ROP compared with only four of the 12 units in the public sector. Conclusions: ROP is the leading cause of blindness in children in Mexico despite national guidelines being in place. Health policies promoting primary prevention through improved neonatal care need to be implemented. Advocacy is required so that the time ophthalmologists spend screening and treating ROP is included in their job description and hence salaried.